2007
DOI: 10.1007/s00595-007-3558-9
|View full text |Cite
|
Sign up to set email alerts
|

Adenomyomatous Hyperplasia of the Common Bile Duct: Report of a Case

Abstract: Adenomyomatous hyperplasia is most commonly found in the stomach, gallbladder, duodenum, and jejunum, while it is rarely found in the extrahepatic bile duct. A 62-year-old woman was referred to our institution with a diagnosis of common bile duct (CBD) stenosis which had been detected by endoscopic retrograde cholangiopancreatography (ERCP). Abdominal computed tomography with contrast medium revealed a thickening of the wall of the lower CBD, and this lesion was weakly enhanced by contrast medium in the arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…However, if it is difficult to distinguish it from the malignancy preoperatively, a radical surgical procedure may be performed as a treatment alternative, although that carries the potential for complications. 2 This case showed that the imaging evaluations for jaundice in a middle-aged male patient suggested a malignant CBD obstruction without any mass, while histopathologic reports of repeated endobiliary biopsies and aspiration showed no evidence of malignancy. The patient decided to undergo the surgery despite strong recommendations to observe the progression of biliary stricture as there was a high probability of a benign lesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if it is difficult to distinguish it from the malignancy preoperatively, a radical surgical procedure may be performed as a treatment alternative, although that carries the potential for complications. 2 This case showed that the imaging evaluations for jaundice in a middle-aged male patient suggested a malignant CBD obstruction without any mass, while histopathologic reports of repeated endobiliary biopsies and aspiration showed no evidence of malignancy. The patient decided to undergo the surgery despite strong recommendations to observe the progression of biliary stricture as there was a high probability of a benign lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the cases were diagnosed after surgical resection because diagnosis based on variable imaging modalities and endoscopic biopsy was difficult. 2 There are no long-term tracking data or studies with large samples of the relationship between biliary malignancies and adenomyomatous hyperplasia of extrahepatic bile duct, but the prognosis of adenomyomatous hyperplasia of the extrahepatic bile duct is expected to be similar to that of adenomyomatous hyperplasia of gallbladder because of the histological similarity. 7 At this time, adenomyomatous hyperplasia is not considered to be pre-cancerous nor does the condition increase the probability of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenomyomas are common in the stomach, gallbladder and jejunum but are very unusual in the common bile duct or the ampullary region [11]. Adenomyomas of the extrahepatic bile duct are defined as non-neoplastic, tumor-like localized lesions characterized by glandular and myomatous hyperplasia without cellular atypia [12].…”
Section: Discussionmentioning
confidence: 99%
“…As different terms are used in the literature to describe the same histological lesion, the true incidence of adenomyomas of the ampullary region is unclear. In the literature, 30 cases of adenomyomas of the ampulla of Vater and 13 cases of the extrahepatic bile duct have been reported [11,13]. Adenomyomas are usually diagnosed by histopathologic examination after surgery.…”
Section: Discussionmentioning
confidence: 99%